The bactericidal effect of shock waves - Leighs, James Allen; Appleby-Thomas, Gareth J.; Wood, David C.; Goff, Michael J.; Hameed, Amer; Hazell, Paul J. (Institute of Physics (IOP), 2014)
There are a variety of theories relating to the origins of life on our home planet, some of which discuss the possibility that life may have been spread via inter-planetary bodies. There have been a number of investigations into the ability of life to withstand the likely conditions generated by asteroid impact (both contained in the impactor and buried beneath the planet surface). Previously published data regarding the ability of bacteria to survive such applied shockwaves has produced conflicting conclusions. The work presented here used an established and published technique in combination with a single stage gas gun, to shock and subsequently recover Escherichia coli populations suspended in a phosphate buffered saline solution. Peak pressure across the sample region was calculated via numerical modelling. Survival data against peak sample pressure for recovered samples is presented alongside control tests. SEM micrographs of shocked samples are presented alongside control sets to highlight key differences between cells in each case.